2021
DOI: 10.3389/fimmu.2021.740790
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Antiangiogenic Therapy Plus Immune Checkpoint Inhibitors Combined With Intratumoral Cryoablation for Hepatocellular Carcinoma

Abstract: BackgroundHepatocellular carcinoma (HCC) is a common gastrointestinal malignancy with high incidence and poor prognosis. Common treatment methods include surgery, transcatheter arterial chemoembolization (TACE), ablation, and targeted therapy. In recent years, combination treatment with antiangiogenic therapy and immune checkpoint inhibitors has made great progress in the treatment of advanced HCC. Here, we report the case of a patient with HCC who achieved a durable benefit from anti-vascular therapy and immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…AQP inhibitors (mercuric chloride) combinate with cryoablation significantly reverses resistance and improve treatment effects ( 109 , 110 ), which supported AQP inhibitors in combination with cryoablation-immunotherapy in clinical practice. Combined cryoablation with Toripalimab (anti-PD-1) and Lenvatinib (anti-angiogenic agent) in a metastatic HCC patient also achieved CR at 7 months after treatment, and PFS as 24 months ( 111 ). Compared with cryoablation-chemotherapy and cryoablation-DC-CIK cell therapy, combinate treatment of cryoablation-immunotherapy-chemotherapy showed the longest median OS estimation in metastatic NSCLC (27 months, 95%CI, 26.6-37.0, P <0.001) ( 112 ).…”
Section: Challenges For Combining Ablation and Immunotherapymentioning
confidence: 98%
“…AQP inhibitors (mercuric chloride) combinate with cryoablation significantly reverses resistance and improve treatment effects ( 109 , 110 ), which supported AQP inhibitors in combination with cryoablation-immunotherapy in clinical practice. Combined cryoablation with Toripalimab (anti-PD-1) and Lenvatinib (anti-angiogenic agent) in a metastatic HCC patient also achieved CR at 7 months after treatment, and PFS as 24 months ( 111 ). Compared with cryoablation-chemotherapy and cryoablation-DC-CIK cell therapy, combinate treatment of cryoablation-immunotherapy-chemotherapy showed the longest median OS estimation in metastatic NSCLC (27 months, 95%CI, 26.6-37.0, P <0.001) ( 112 ).…”
Section: Challenges For Combining Ablation and Immunotherapymentioning
confidence: 98%
“…The data on cryoablation plus ICIs are limited. However, in a case report of a patient with metastatic HCC post-surgery, cryoablation with lenvatinib and toripalimab led to a complete response after 7 months post-treatment and a PFS of 24 months at the time of manuscript submission [272]. Another study found that cryoablation with DCs-cytokineinduced killer cell immunotherapy in metastatic HCC led to a significantly higher median OS than in the cryotherapy group alone (p < 0.05) [273].…”
Section: Ablation Plus Icismentioning
confidence: 99%
“…Thus, TKIs might enhance the antitumor effects and reduce drug resistance to ICIs 99 , 100 . Li et al reported that a patient with metastatic HCC who had disease recurrence following surgery and then received CRA followed by combined lenvatinib and toripalimab achieved a complete response after 7 months of treatment and a PFS of 24 months in the latest reported 101 .…”
Section: Ablation Combined With Systematic Therapy- Potential To Chan...mentioning
confidence: 99%